LITERATURE REVIEW OF HIGH-GRADE INDUSTRIAL SALT PRODUCTION USING MEMBRANE TECHNOLOGY - Purnomo Ajie, Lintang
Industrial salt is an important chemical for various chemical industries in Indonesia. Indonesia's industrial salt needs in 2020 reached 3,744,655 tons or 83.9% of the national requirement. Ironically, the percentage of industrial salt fulfillment through local production is only 21.72%. One of the solutions to increase local salt production is the development of production technology. Therefore, this study seeks to conduct a literature review on alternative technologies for industrial salt production by applying membrane technology. The research was conducted through a literature review on the method of purification, concentration, and crystallization of seawater using available membrane technology. Studies show that the best feed purification method is through the integration of precipitation softening (PS) and ultrafiltration membrane (UF) with the rejection of Ca, Mg, and total dissolved solids (TDS) close to 100%. The recommended technology for feed concentration is a distillation membrane (MD) with water recovery up to 87,6% and capable of producing retentates up to saturation concentrations. The recommended crystallization process is integrated crystallization in the same MD unit with 2%-weight pure NaCl seeding. The yield of crystals by this method is estimated to be 34% of the feed TDS or 28 kg/m3 with a purity >99%. Economic analysis for the PS-UF-RO-MD scheme shows a cost of salt (COS) of $0.53/kg NaCl. The percentage of COS in this scheme shows that the highest capital expenditure (CAPEX) is in the RO process at 69% and the highest operational expenditure (OPEX) is in the MD process at 48%. On the other hand, the PS-UF-MD scheme shows a COS of $0.39/kg NaCl. The highest percentage of CAPEX and OPEX costs in this scheme is in the MD process, namely 52% and 73%, respectively. The COS of the PS-UF-MD scheme has a lower value than the local salt price, $0.4 to $0.6/kg NaCl. Thus, this scheme is considered to have the potential to become an alternative technology for local industrial salt production in the future with the support of further studies.